Bonjour voici 6 expressions a réduire je l'est déjà fait mais je veux être sur :

A= (2x-5)(3-x)

B=(3x-4)²

C= (4x+9) (4x-9)

D=(8+5x)²

E= (-3x+4)(x+2) + (5x+1)(x-2)

F= (2x+5)(-x+2) - (x-3)(-3x+4)

J'offre 14 point

2

Réponses

2014-10-10T16:47:32+02:00
A= (2x-5)(3-x)A = 6 x - 2 x² - 15 + 5 xA = - 2x² + 11 x -15B=(3x-4)²b = 9 x² - 24 x +16
C= (4x+9)(4x-9)c = 16 x² - 81D=(8+5x)²d = 64 + 80 x + 25x²E= (-3x+4)(x+2) + (5x+1)(x-2)e = - 3x² - 6x + 4x + 8 - ( 5x² - 10x +x - 2)e = - 3x² - 2 x + 8 - 5 x² +10 x - x + 2
e = - 8 x² + 7x + 10
F= (2x+5)(-x+2) - (x-3)(-3x+4)f = - 2 x² + 4 x - 5x + 10 - ( - 3x² + 4 x + 9 x - 12)
f = - 2x ² - x +10 + 3x ² - 4x - 9x +12
f = x² - 14 x + 22
A= (2x-5)(3-x)A = 6 x - 2 x² - 15 + 5 xA = - 2x² + 11 x -15B=(3x-4)²b = 9 x² - 24 x +16
C= (4x+9)(4x-9)c = 16 x² - 81D=(8+5x)²d = 64 + 80 x + 25x²E= (-3x+4)(x+2) + (5x+1)(x-2)e = - 3x² - 6x + 4x + 8 - ( 5x² - 10x +x - 2)e = - 3x² - 2 x + 8 - 5 x² +10 x - x + 2
e = - 8 x² + 7x + 10
F= (2x+5)(-x+2) - (x-3)(-3x+4)f = - 2 x² + 4 x - 5x + 10 - ( - 3x² + 4 x + 9 x - 12)
- 2x ² - x +10 + 3x ² - 4x - 9x +12
x² - 14 x + 22
2014-10-10T17:03:57+02:00
A = (2x - 5) (3 - x)
A = 6x  - 2X² - 15 + 5X
A = - 2x² + 11 x -15

B =(3x - 4)²
B = 9x² - 24x +16

C = (4x + 9) (4x - 9)
C = 16x² - 81

D = (8 + 5x)²
D = 64 + 80x + 25x²

E= (-3x + 4) (x + 2) + (5x + 1) (x - 2)
E = - 3x² - 6x + 4x + 8 + 5x² - 10x + x - 2
E = - 3x² + 5x² - 6x - 10x + 4x + x + 8 - 2
E = 2x² - 11x + 6

F = (2x + 5) (- x + 2) - (x - 3) (-3x + 4)
F = - 2x² + 4x - 5x + 10 - (- 3x² + 4x + 9x - 12)
F = - 2x ² - x + 10 + 3x ² - 4x - 9x + 12
F = x² - 14x + 22